2015
DOI: 10.17557/tjfc.58656
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Fertigation to Improve Nitrogen Use Efficiency and Crude Protein on Silage Corn

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 36 publications
5
16
0
Order By: Relevance
“…This could be explained as such that dry matter (DM) accumulation increased by irrigation (Kiziloglu et al, 2009). Parallel to finding of Yolcu and Cetin (2015), decreasing dry matter contents were observed in this study with decreasing irrigation water quantities. Similarly, Li et al (2004) reported 49% increase in maize yield with full irrigation (295 mm).…”
Section: Dry Matter (Dm)supporting
confidence: 87%
See 4 more Smart Citations
“…This could be explained as such that dry matter (DM) accumulation increased by irrigation (Kiziloglu et al, 2009). Parallel to finding of Yolcu and Cetin (2015), decreasing dry matter contents were observed in this study with decreasing irrigation water quantities. Similarly, Li et al (2004) reported 49% increase in maize yield with full irrigation (295 mm).…”
Section: Dry Matter (Dm)supporting
confidence: 87%
“…While the present findings were quite similar to ones reported by Yolcu and Cetin (2015), they were higher than the findings of the other researchers. Such differences between these studies were because of differences in irrigation methods, irrigation programs, local climate, soil and cultural techniques.…”
Section: Dry Matter (Dm)supporting
confidence: 81%
See 3 more Smart Citations